2010
DOI: 10.1128/aem.00741-10
|View full text |Cite
|
Sign up to set email alerts
|

Production of a New Thiopeptide Antibiotic, TP-1161, by a Marine Nocardiopsis Species

Abstract: Twenty-seven marine sediment-and sponge-derived actinomycetes with a preference for or dependence on seawater for growth were classified at the genus level using molecular taxonomy. Their potential to produce bioactive secondary metabolites was analyzed by PCR screening for genes involved in polyketide and nonribosomal peptide antibiotic synthesis. Using microwell cultures, conditions for the production of antibacterial and antifungal compounds were identified for 15 of the 27 isolates subjected to this screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(105 citation statements)
references
References 47 publications
(51 reference statements)
0
98
0
3
Order By: Relevance
“…Therefore screening the PKS, NRPS and halogenase genes has been applied to estimate diversity in antimicrobial production (Ayuso-Sacido & Genilloud, 2005;Gao & Huang, 2009;Mets€ a-Ketel€ a et al, 2002. Strains that tested positive in the biosynthetic gene screening produced secondary metabolites with novel structures and greater diversity, making the biosynthetic gene screening a valuable tool for selecting secondary metabolite producers (Baba et al, 2015;Engelhardt et al, 2010;Sun et al, 2012). A possible caveat in relying on gene analyses or antimicrobial assays only lies in the notion that actinobacterial strains with no detectable biosynthetic genes may show, and strains carrying the genes do not necessarily show antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore screening the PKS, NRPS and halogenase genes has been applied to estimate diversity in antimicrobial production (Ayuso-Sacido & Genilloud, 2005;Gao & Huang, 2009;Mets€ a-Ketel€ a et al, 2002. Strains that tested positive in the biosynthetic gene screening produced secondary metabolites with novel structures and greater diversity, making the biosynthetic gene screening a valuable tool for selecting secondary metabolite producers (Baba et al, 2015;Engelhardt et al, 2010;Sun et al, 2012). A possible caveat in relying on gene analyses or antimicrobial assays only lies in the notion that actinobacterial strains with no detectable biosynthetic genes may show, and strains carrying the genes do not necessarily show antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis of thiazolylpyridine macrocyclic ring size as determinant of ribosomal versus elongation factor targeting is not yet known. One additional macrocyclic ring size in the thiopeptide antibiotic class is represented by the berninamycins, sulfomycin (19), thioplabin (20), and TP-1161A (21,22). This class has a unique oxazolyl-thiazolyl-pyridine core embedded in a 35-membered (13-residue) peptidyl macrocycle ( Fig.…”
mentioning
confidence: 99%
“…Many studies reported that the actinobacterial genera like Nocardiopsis species had the ability to produce a wide spectrum of antimicrobial and anticancer metabolites that had higher ability to inhibit cancer cell lines in comparison with another source like plant products having antioxidant activity and they inhibit cancer cell lines [1][2][3][4][5][6][7][30][31][32][33]. …”
Section: Fig 1: Gel Filtration Chromatography Of Feather Meal-cementmentioning
confidence: 99%
“…Nocardiopsis species produced a novel antibiotic like naphthospironones (antimicrobial and anticancer compounds) [3], apoptolidins (selective anticancer agents) [4], griseusins (antimicrobial and anticancer compounds) [5], thiopeptides (antibiotic) [6] and lipopeptides (surfactants) [7]. This actinobacterium is thus of considerable biotechnological importance and can serve as potential sources of natural products and new metabolites in the future.…”
Section: Introductionmentioning
confidence: 99%